Krāpšanas pirmstiesas izmeklēšanas kārtība un īpatnības - Griņeviča, Nadežda (Latvijas Universitāte, 2012)
Diplomdarba tēma - „Krāpšanas pirmstiesas izmeklēšanas kārtība un īpatnības”. Darba mērķis - studējot tiesisko regulējumu, dažādas publikācijas un viedokļus, juridisko literatūru, tiesībsargājošo institūciju materiālus, aplūkot un izpētīt krāpšanas raksturojumu un pirmstiesas izmeklēšanas veikšanas kārtību un īpatnības krāpšanas lietās, kā arī noskaidrot tiesiskā regulējuma nepilnības un problēmas šajā jomā. Lai sasniegtu nosprausto darba mērķi, autore izvirzīja vairākus darba uzdevumus –krāpšanas raksturojuma un tās īpatnību, kas atšķir to no citiem noziedzīgiem nodarījumiem izpēte; pirmstiesas izmeklēšanas kārtības un tas īpatnības krāpšanas lietās izpēte un analīze; sākotnējo izmeklēšanas darbību, kuras ir veicamas krāpšanas lietās analīze; problēmu, kuras pazemina to efektivitāti vai rāda to pielietošanas neiespējamību atrašana. Minētā mērķa sasniegšanai darbs veidots no trim nodaļām. Pirmajā nodaļā apskatīts krāpšanas jēdziens un raksturojums krimināltiesiskajā un kriminālistiskajā aspektā un saistītām ar to krāpšanas kvalifikācijas problēmas. Otrā nodaļa veltīta pirmstiesas izmeklēšanas veikšanas kārtības un īpatnību izpētei, savukārt trešajā nodaļā tiek apskatīta sākotnējo izmeklēšanas darbību veikšana būtība krāpšanas izmeklēšanā un to specifiskās iezīmes. Diplomdarba nobeigumā autore izvirzīja darba rakstīšanas gaitā aktualizējušos problēmjautājumus (secinājumus), kā arī piedāvāja savus priekšlikumus to risināšanai / novēršanai.

The theme of the diploma paper is „Procedure and peculiarities of pre-trial investigation of the fraud”. Pre-trial investigation has the peculiarities which become intelligible due to the analysis of its legal-criminal and forensic characteristics with the further examination of the tactics of conduction of investigatory actions, on the basis of which the aim of the diploma paper is to discover the normative inaccuracies and problems in this field through studying such aspects as the legislation (basis), different kinds of publications from the juridical literature, the practical work experience of law enforcement authorities, making analysis and studying the characteristics of the fraud according with Criminal law 177.article, as well the procedure and peculiarities of pre-trial investigation of the fraud. To achieve the aim of the paper the author raises a number of tasks – research of legal-criminal and forensic characteristics of the fraud, which makes it different from other types of crimes, also studying and analyzing of the procedure and peculiarities of pre-trial investigation of the fraud, which include the analysis of primary investigatory actions, taking place during the primary stage of pre-trial investigation of the fraud, as well as revelation of the problems which diminish the effectiveness of its application. The first part of the paper provides the corpus delicti of the fraud, reveals the peculiarities of the fraud, which make it different from other types of crimes; tricks and methods of the fraud, the author also reveals the problems connected with the qualification of the fraud and their possible solutions. The second part of the paper deals with the analysis of the procedure and peculiarities of pre-trial investigation of the fraud, and the aim of this is to discover the verity and find evidences. The problems of pre-trial investigation and their possible solutions are discovered there as well. The third part of the paper contains examination and methods of the tactical application of primary investigatory actions and the way of their legal procedure, also importance and peculiarities of the investigation of the fraud. The problems of their application in pre-trial investigation are discovered there as well. Due to the variety of different types of the fraud, the problems stated in the process of the research in the frame of this paper, are not exhaustive. Those problems ask for further theoretical and legal elaboration.
Procedure and pecualiarities of pre-trial investigation of the fraud
Keywords: Juridiskā zinātne